Early changes in glial reactivity and lipid peroxidation in diabetic rat retina: effects of melatonin - Baydas, G; Tuzcu, M; Yasar, A; Baydas, B (Springer-Verlag Italia Srl, 2004)
Diabetes mellitus, the most common serious metabolic disorder, is characterized by functional and structural changes in the peripheral and central nervous systems. Glial cells provide structural and metabolic support for retinal neurons. During diabetes, one of the early pathogenic events is retinal glial reactivity. We studied the effects of melatonin, which is known to reduce oxidation-based neurotoxicity, on glial reactivity and lipid peroxidation in the retina of diabetic rats. Diabetes was induced by a single injection of streptozotocin (STZ), and these diabetic rats were treated daily either with melatonin (10 mg/kg) or saline vehicle. After 6 weeks of diabetes, we determined the extents of lipid peroxidation and glial C, reactivity in retina. Lipid peroxidation, measured on the basis of malondialdehyde and 4-hydroxyalkenals concentrations, was increased in diabetic rats (p<0.01) and this increase was prevented by melatonin treatment (p<0.05). Furthermore, gial reactivity, determined immunohistochemically from the levels of glial fibrillary acid protein (GFAP), was also increased significantly (p<0.01). Melatonin administration partially prevented this increase in GFAP content (p<0.05). In conclusion, glial reactivity is an early pathogenic event in diabetic retina and both reactive gliosis and accumulation of malondialdehyde and 4-hydroxyalkenals are prevented by melatonin supplementation.
Keywords: melatonin; diabetes; retina; glial fibrillary acidic protein; lipid peroxidation